2020
DOI: 10.2217/bmt-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Lesions of the Breast: A Review

Abstract: Papillary breast lesions are rare breast tumors that comprise a broad spectrum of diseases. Pathologically they present as mass-like projections attached to the wall of the ducts, supported by fibrovascular stalks lined by epithelial cells. On mammogram they appear as masses that can be associated with microcalcifications. Ultrasound is the most used imaging modality. On ultrasound papillary lesions appear as homogeneous solid lesions or complex intracystic lesions. A nonparallel orientation, an echogenic halo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 80 publications
(171 reference statements)
1
11
0
Order By: Relevance
“…Previous studies have demonstrated that CNB have a very high diagnostic accuracy, with a sensitivity, specificity, positive predictive value and negative predictive value of 90% or higher (Nunez et al, 2020). In the present study, the accuracy, sensitivity and specificity of CNB in the diagnosis of PBLs/Ns were about 90% with a PPV of 98.5%.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies have demonstrated that CNB have a very high diagnostic accuracy, with a sensitivity, specificity, positive predictive value and negative predictive value of 90% or higher (Nunez et al, 2020). In the present study, the accuracy, sensitivity and specificity of CNB in the diagnosis of PBLs/Ns were about 90% with a PPV of 98.5%.…”
Section: Discussionsupporting
confidence: 58%
“…Papillary breast neoplasms (PBNs) are a heterogeneous group of epithelial tumors composed mostly of papillae. These lesions account for less than 3% of breast tumors and their classification rests on the characteristics of the epithelium and the presence and distribution of the myoepithelial cells along the papillae and around the tumor (Nunez et al, 2020;Brogi and Krystel-Whittemore, 2021). Based on the most updated World Health Organization (WHO) classification of breast neoplasms, PBNs include: intraductal papilloma (IDP) with or without atypia, papillary ductal carcinoma in situ (papillary DCIS), encapsulated papillary carcinoma (EPC), solid-papillary carcinoma (SPC; in situ and invasive), and invasive 2019; Brogi and Krystel-Whittemore, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant papillary neoplasm of the breast includes several microscopically distinct lesions such as DCIS (Ductal Carcinoma in Situ) arising in intra ductal papilloma, papillary DCIS, encapsulated papillary carcinoma, solid papillary carcinoma, and invasive papillary carcinoma. All malignant papillary lesions of the breast lack an intact myoepithelial cell layer (MCL) within the papillae or at the periphery of the tumor [6].…”
Section: Discussionmentioning
confidence: 99%
“…Papillary tumours of the breast are rare and heterogenous lesions of the breast accounts for less than 3% of all breast tumours (1). The 5th edition of World Health Organization (WHO) Classification of Breast Tumors (2), describes these tumours in detail ranging from benign intraductal papilloma to invasive papillary carcinoma (IPC).…”
Section: Introductionmentioning
confidence: 99%